Trends of Agenda Setting Research: A Bibliometric and A Thematic Meta-Analysis - Ari Sulistyanto; Achmad Jamil (Universitas Muhammadiyah Yogyakarta, 2023)
Agenda-setting studies continue to experience an evolutionary process. It goes beyond its initial assumption, which is the transfer of meaning from the media agenda to the public agenda, and expands to experience replication. Recent literature studies regarding the mapping of agenda-setting studies have not been carried out much. Therefore, this study aims to find trends in agenda setting research in the global scope based on agenda setting data from 2014 to 2022. Trends in the global scope are interesting to study to see agenda-setting studies today. This study uses the Bibliometric Analysis and a thematic theme analysis approaches. The research show that politics-related topics have dominated over the last eight years. The use of network agenda-setting (NAS) and agenda-setting intermedia (IAS) theory, content analysis and survey, and Twitter are essentials part of this study. The entire development of digital media is slowly leaving conventional media. Therefore, future studies, in the presence of a variety of media platforms, need to design alternative models and methodologies that can explain the power of influence of each media in shaping the agenda-setting effect.